Mecanismos de movimentação animal embasados na memória espacial - Berbert, Juliana Militão da Silva [UNESP] (2013)
The study of population dynamics in space includes a description of the mechanisms of different movement strategies. These strategies are in?uenced by a variety of factors, such as the landscape features, animal behavior and physiology. One of the most active areas that focuses on the spatial dynamics of populations is the incorporation of these factors into the description of population dynamics. Namely, one seeks ways to incorporate these in?uences to individual models of animal movements, and then, determine the corresponding population level models describing the patterns of space and time use. This thesis refers to the study of spatial redistribution of animals populations. We are interested in knowing how the heterogeneity of the space and the in?uence of spatial memory of individuals affect the dynamic dispersion of a population, related to diffusion or anomalous diffusion, and the generation of patterns, related to ecological behaviors such as sedentarism, migration and nomadism. With this purpose, we have developed two models, one is centred on individuals and the other is at the population level. For the model centered on individuals, we have de?ned movement rules that depend on the spatial memory of individuals that move on a dynamic heterogeneous environment. From these rules we have performed computer simulations and we associate our results to patterns of ecological behaviors. To model the population level, we have also de?ned rules for movement dependent on the memory of individuals and we “translated” these rules into partial differential equations. Through numerical analysis we could associate our results to the diffusive and superdiffusive dispersal patterns. In this thesis, we use the tools of physics and mathematics and biology principles to understand the mechanisms for animals movement and to ?nd a way to relate them to patterns of population redistribution. Our results...